Potential application mechanism of traditional Chinese medicine in treating immune checkpoint inhibitor-induced colitis - Wang, Jing; Guo, Ziyue; Shen, Mengyi; Xie, Qi; Xiang, Hongjie (Frontiers in Immunology, 2024)
Cancer ranks among the foremost causes of mortality worldwide, posing a significant threat to human lives. The advent of tumor immunotherapy has substantially transformed the therapeutic landscape for numerous advanced malignancies, notably non-small cell lung cancer and melanoma. However, as immune checkpoint inhibitors (ICIs) are increasingly applied in clinical settings, a spectrum of undesired reactions, termed immune-related adverse events (irAEs), has emerged. These adverse reactions are associated with immunotherapy and can result in varying degrees of harm to the human body. Among these reactions, Immune checkpoint inhibitor-induced colitis (ICIIC) stands out as one of the most prevalent clinical adverse events. In contemporary times, traditional Chinese medicine (TCM) has demonstrated remarkable efficacy in addressing various maladies. Consequently, investigating the potential application and mechanisms of Chinese medicine in countering immune checkpoint inhibitor-induced colitis assumes significant importance in the treatment of this condition.